Upper Eyelid Approach for the Reconstruction of Isolated Fractures of the Anterior Wall of the Frontal Sinus. Issue 7 (October 2018) - Nguyen, David; Hakimi, Michael; Sinha, Sumedha R.; Martin, Mark
Abstract : Abstract: The management of frontal sinus fractures can vary widely depending on involvement of the anterior wall, the posterior wall, and the frontonasal duct. The main morbidity associated with isolated anterior wall fractures is an aesthetic deformity. Treatment includes coronal, endoscopic, and transcutaneous approaches. However, each has reported limitations and associated risks of iatrogenic injuries. In this paper, the authors discuss a novel approach through the upper eyelid crease and examine 4 cases where it is utilized for anterior frontal sinus wall, superior orbital rim, and orbital roof fracture repair.